Mother's Role In Motherhood Movie (2009) Directed By Katherine Dieckmann: A Feminist Approach - Zuliani, Iin Rohmatun Anita (2012)
The study is to reveal how mother's role is reflected in Motherhood directed by Katherine Dieckmann published in 2009. The objective of the study is to analyze the structural elements in the movie and to analize mother's role of the movie based on feminist approach. The researcher employs the descriptive qualitative research as a type of the research. The data sources divided into two, namely primary data source and secondary data source. The primary data source is the events of the movie and script of Motherhood and the secondary data source is biography of character. The object of the study is a movie Motherhood directed by Katherine Dieckmann. The method of collecting data are watching the movie, taking note the important data, arranging the data based on category of elements of literature review and the last is looking for the supporting data. The technique of analyzing data is descriptive analysis. The result of the study is as follows. First, based on the structural analysis, Katherine Dieckmann delivers the theme is about life is full with choice, human being has freedom to choose their role and opportunity. The structural elements are related each other and form a unity. Second, based on the feminist analysis, Katherine Dieckmann reflect woman's position, woman's role, woman's right, and woman's participation in life condition of a mother. Dieckmann considers that mother has equal opportunity and right in a family.